The prognostic power of gene mutations in thyroid cancer - Sara Ahmadi; Iñigo Landa (Endocrine Connections, 2024)
The introduction and generalization of next-generation sequencing techniques have significantly increased the identification of mutations in thyroid tumors from multiple patient cohorts. The understanding of the association between specific mutations and clinical outcomes is gradually leading to individualizing the care of patients with thyroid cancer. BRAFV600 is the most common mutation seen in thyroid cancer patients and unequivocally predicts malignancy, but when considered in isolation, it is not recommended to be used as an independent prognostic factor. Mutations in RAS are the second most common alterations in thyroid cancer but can be found in benign and malignant lesions. Rearrangements involving receptor tyrosine kinases, primarily RET, are found in a subset of thyroid tumors without mutations in either BRAF or RAS. The assessment of additional mutations is increasingly employed in thyroid cancer prognostication. The coexistence of BRAF with alterations in genes such as PIK3CA, TERT promoter, or TP53 is associated with less favorable outcomes. Similar studies have also shown that additional oncogenic mutations in RAS-mutant thyroid carcinoma, such as those affecting the EIF1AX gene, likely predict a more aggressive clinicopathologic behavior. Overall, emerging evidence suggests that the co-occurrence of specific alterations in defined genes with BRAF or RAS mutations can become prognostic tools and useful predictors of thyroid tumor aggressiveness.